2015
DOI: 10.1097/hjh.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control and risk profile in poststroke survivors

Abstract: We found a high prevalence and poor control of major cardiovascular risk factors in patients surviving their first-ever ischemic stroke, thus showing poor implementation of guidelines for secondary prevention in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
8
0
7
Order By: Relevance
“…Com relação às estimativas internacionais de prevalência de hipertensão, algumas revisões e metanálises têm sido conduzidas em nível mundial, apresentando grande abrangência de dados [42][43][44][45][46][47][48] . A metanálise mais abrangente e bem conduzida sobre a prevalência da hipertensão em nível mundial foi publicada por Mills et al 42 , englobando 135 estudos de 90 países distintos e uma amostra final de quase um milhão de participantes.…”
Section: Discussionunclassified
“…Com relação às estimativas internacionais de prevalência de hipertensão, algumas revisões e metanálises têm sido conduzidas em nível mundial, apresentando grande abrangência de dados [42][43][44][45][46][47][48] . A metanálise mais abrangente e bem conduzida sobre a prevalência da hipertensão em nível mundial foi publicada por Mills et al 42 , englobando 135 estudos de 90 países distintos e uma amostra final de quase um milhão de participantes.…”
Section: Discussionunclassified
“…Confirming the dominant importance of high blood pressure, the authors report that they found hypertension in 92% of stroke survivors and 72% of population controls. Although use of blood pressure-lowering drugs was common in both the groups, 80% in poststroke survivors and 57% in the controls, effective blood pressure control, defined as blood pressure 140/90 mmHg or less, was found only in 43% of stroke survivors and 44% of population controls [5]. The significant predictors of good control were use of angiotensin-converting enzyme inhibitors, number of blood pressure-lowering drugs used, female sex and university education.…”
mentioning
confidence: 89%
“…On the other hand, about three-quarters of survivors did take antiplatelet agents, including aspirin. Another disappointment was the fact that about one-third of the survivor group continued to smoke and 40% were obese [5]. The authors conclude that these findings reflect poor implementation of guideline recommendations by clinicians, particularly general practitioners who treat the majority of stroke survivors.…”
mentioning
confidence: 99%
See 2 more Smart Citations